Irrational exuberance and herding in financial markets - Christopher Boortz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
In the context of a two-state, two-trader financial market herd model introduced by Avery and Zemsky (1998) we investigate how informational ambiguity in conjunction with waves of optimism and pessimism affect investor behavior, social learning and price dynamics. Without ambiguity, neither herding nor contrarianism is possible. If there is ambiguity and agents have invariant ambiguity preferences, only contrarianism is possible. If on the other hand ambiguity is high and traders become overly exuberant (or desperate) as the asset price surges (or plummets), we establish that investor herding may drive prices away from fundamentals with economically relevant probability.
Keywords: D81; D82; G12; G14; 330; Social Learning; Herding; Contrarianism; (Partial) Informational Cascade; Ambiguity; Choquet Expected Utility; NEO-Additive Capacities